Investigations on the influence of the addition of carbon dioxide on the production and properties of rapidly set wood-cement composites. - H. Simatupang, Maruli

(untitled)
This paper gives a short description of the manufacturing process of cement particle boards Production methods currently used are characterized by a pressing time of boards of about 8 h Also, flakes from only a limited number of wood species are suitable as reinforcing material.